Geothermal energy as a source of electric power : thermodynamic and economic design criteria - Milora, Stanley L.; Tester, Jefferson W. (Cambridge, Mass.: MIT Press, 1976)
Examines geothermal power resources in detail, its magnitude and environmental factors involved in its development.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Geothermal engineering; Elektriciteitsvoorziening; Thermodynamics; Geothermal resources; Geothermische energie; Techniques géothermiques.; Thermodynamique; Énergie géothermique.; Techniques géothermiques.; Thermodynamique; Énergie géothermique.; Électricité -- -- Production